2003
DOI: 10.3989/scimar.2003.67s269
|View full text |Cite
|
Sign up to set email alerts
|

Geographical patterns of seabird attendance to a research trawler along the Iberian Mediterranean coast

Abstract: SUMMARY: The attendance of seabirds to a research trawler along the Mediterranean coast of the Iberian Peninsula was monitored during six demersal surveys (MEDITS project). Cruises were performed in late spring during the period 1994-1999. Twenty seabird species were recorded, including both breeders and migrants. The four most common species behind the boat were local breeders, namely the Balearic shearwater Puffinus mauretanicus, Cory's shearwater Calonectris diomedea, Audouin's gull Larus audouinii and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 11 publications
(9 reference statements)
3
19
0
Order By: Relevance
“…Canyons have also been shown to provide habitat for spawning females of pelagic and benthic species of commercial interest (Farrugio, 2012). Other faunal components of marine ecosystems, including mammals and marine birds, also use canyons, for example, as feeding grounds (Abelló et al, 2003;Garcia and Thomsen, 2008;Roditi-Elasar et al, 2013;Moors-Murphy, 2014). Habitat diversity and specific abiotic characteristics enhance the occurrence of high levels of biodiversity in some canyons (Vetter and Dayton, 1998;McClain and Barry, 2010;Company et al, 2012;De Leo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Canyons have also been shown to provide habitat for spawning females of pelagic and benthic species of commercial interest (Farrugio, 2012). Other faunal components of marine ecosystems, including mammals and marine birds, also use canyons, for example, as feeding grounds (Abelló et al, 2003;Garcia and Thomsen, 2008;Roditi-Elasar et al, 2013;Moors-Murphy, 2014). Habitat diversity and specific abiotic characteristics enhance the occurrence of high levels of biodiversity in some canyons (Vetter and Dayton, 1998;McClain and Barry, 2010;Company et al, 2012;De Leo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…5, Millot 1999 Breeding Balearic shearwaters likely use the same foraging grounds year after year as the western Mediterranean is characterised by a relatively stable coastal circulation, and overall chl a values may not differ greatly between years (Gordoa et al 2008). In fact, the location of resources at large and intermediate scales appears reasonably predictable for pelagic seabirds over long time periods in the Mediterranean because they associate to the same mesoscale features along the Iberian continental shelf during different years (Arcos & Oro 2002, Abelló et al 2003, Louzao et al 2006a). The use of tracking devices may link foraging trip characteristics to fitness parameters such as breeding performance.…”
mentioning
confidence: 99%
“…Some other studies in the same area, however, have shown that gulls still forage at sea even when trawlers do not operate (Oro, 1995b;Abelló and Oro, 1998a;Abelló et al, 2003), probably taking advantage of the relatively high natural production of the continental shelf (Estrada, 1996), or in association with purse seiners (Arcos et al, 2001). Our results, then, are probably the consequence of birds leaving the colony after reproductive failure (Oro and Martínez-Vilalta, 1994), rather than a change in foraging behaviour associated with the trawling moratoria.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the foraging ranges were probably smaller here than in other colonies (Burger and Gochfeld, 1996;Oro, 1998a, Baccetti et al, 2000. Maximum foraging activity (as number of birds outside the colony) took place every day in mid-morning and mid-afternoon, whereas minimum activity occurred at midnight, suggesting that gulls may adjust their timetable to that of trawlers (Castilla and Jiménez, 1995;Oro, 1995a;González-Solís et al, 1999;Abelló et al, 2003), but also to that of purse-seiners or diel (vertical) migrations of cupleids (with one peak at dawn and another at dusk), which would explain why some birds leave the colony at or just before dawn, or arrive just before midnight. In the study area, Audouin's gulls probably exhibited a more marked pattern of diurnal activity than in other areas where fishing activity is not relevant for gulls (Gonzalez-Solis et al, 1999).…”
Section: Discussionmentioning
confidence: 99%